2017
DOI: 10.1038/sigtrans.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB signaling in inflammation

Abstract: The transcription factor NF-κB regulates multiple aspects of innate and adaptive immune functions and serves as a pivotal mediator of inflammatory responses. NF-κB induces the expression of various pro-inflammatory genes, including those encoding cytokines and chemokines, and also participates in inflammasome regulation. In addition, NF-κB plays a critical role in regulating the survival, activation and differentiation of innate immune cells and inflammatory T cells. Consequently, deregulated NF-κB activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

114
4,734
6
73

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 6,120 publications
(4,927 citation statements)
references
References 136 publications
114
4,734
6
73
Order By: Relevance
“…Gene expression of cytokines is closely related to the activation of nuclear factor kappa B (NF-κB), a transcription factor involved in inflammatory processes (Newton and Dixit 2012). Various endo- and exogenous stimuli including reactive oxygen species (ROS), viral and bacterial antigens such as lipopolysaccharide (LPS) induce a downstream signalling cascade through stimulation of various receptors [e.g., toll-like receptors (TLRs)] leading to the activation of NF-κB (Liu et al 2017; Morgan and Liu 2011). Once activated, NF-κB is translocated into the nucleus, where it binds to the promotor region of its target genes and finally induces transcription of several inflammatory mediators (Liu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression of cytokines is closely related to the activation of nuclear factor kappa B (NF-κB), a transcription factor involved in inflammatory processes (Newton and Dixit 2012). Various endo- and exogenous stimuli including reactive oxygen species (ROS), viral and bacterial antigens such as lipopolysaccharide (LPS) induce a downstream signalling cascade through stimulation of various receptors [e.g., toll-like receptors (TLRs)] leading to the activation of NF-κB (Liu et al 2017; Morgan and Liu 2011). Once activated, NF-κB is translocated into the nucleus, where it binds to the promotor region of its target genes and finally induces transcription of several inflammatory mediators (Liu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Various endo- and exogenous stimuli including reactive oxygen species (ROS), viral and bacterial antigens such as lipopolysaccharide (LPS) induce a downstream signalling cascade through stimulation of various receptors [e.g., toll-like receptors (TLRs)] leading to the activation of NF-κB (Liu et al 2017; Morgan and Liu 2011). Once activated, NF-κB is translocated into the nucleus, where it binds to the promotor region of its target genes and finally induces transcription of several inflammatory mediators (Liu et al 2017). Cytokines, such as IL-8, IL-6 and TNF-α are expressed in a NF-κB-dependent manner and function primarily as proinflammatory signals (Tak and Firestein 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It was therefore of interest to test whether AS‐6 could inhibit the expression of transcription factors associated with processes of inflammation. Gene expression of COX‐2 and iNOS, which are well‐known as important proinflammatory proteins, is regulated by downstream signaling of NF‐κB . Therefore, we evaluated the effects of AS‐6 on attenuating LPS‐stimulated NF‐κB nuclear translocation in BV2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…29,32,33 Earlier reports from our laboratory showed an altered expression of S100A8 in endometrial decidual tissue samples of recurrent pregnancy loss cases. 35 No studies till date showed the functional relevance of S100A8 and HMGB1 at maternal-fetal in- To further confirm, whether altered inflammatory and vitamin D signaling in PTB affect the histological architecture of placenta, 35 No studies till date showed the functional relevance of S100A8 and HMGB1 at maternal-fetal in- To further confirm, whether altered inflammatory and vitamin D signaling in PTB affect the histological architecture of placenta,…”
Section: Discussionmentioning
confidence: 99%